Answer:
no solution
Step-by-step explanation:
1/3(12-6x)=4-2x
4-1.3x=4-2x
4=4-0.7x
0=0.7x
ns
The answer is the middle one.
Answer:
x = -10
Step-by-step explanation:
2(x+3) = x-4 --> multiply (x+2) times 2
2x+6 = x - 4 --> subtract x from both sides
x+6 = -4 --> subtract 6 from both sides
x = -10
Answer:
12x + 18y + 6z + 4x - 4z
Step-by-step explanation:
Given the expression : 3(4x + 6y + 2z) + 4(x – z)
To eliminate the parenthesis ; we use the distributive property :
3(4x + 6y + 2z) + 4(x – z) becomes ;
3*4x + 3*6y + 3*2z + 4*x + 4*-z
12x + 18y + 6z + 4x - 4z
Hence,
12x + 4x + 18y + 6z - 4z
16x + 18y + 2z